Good Governance Practices in Godawari Municipality of Lalitpur, Nepal - Pasa, Rajan Binayak; Katuwal, Chiranjibi; Adhikari, Devendra (Nepalese Journal of Development and Rural Studies, 2023)
Good governance is a state management system which offers well-public service deliveries. This study aimed to explain good governance practices in Godawari Municipality in Lalitpur district, Nepal. We applied the post-positivism research paradigm and institutional/exit poll survey research design. The data were generated from 180 sample respondents who were elected leaders, administrative staff, local intellectuals, and service receivers in the municipality, and these were selected purposively and randomly. We applied reliable self-administered questionnaires (0.91> 0.78 Cronbach’s alpha value) consisting of seven indicators: accountability, transparency, participation, the rule of law, corruption, responsiveness, and effectiveness and efficiency. This study is explained through the theoretical insights from decentralization and the new public management theories. This study found that good governance practices in Godawari Municipality were satisfactory and fair. Participation of local youths in the local government is remarkable, and the women elected representatives are more the men. The educational status of the respondents is good, and their level of education and the transparency score in the municipality are positively correlated. Service receivers perceive that political leaders and administrative staffs are mainly responsible for corruption. There exist between the principles of good governance and the practice in the study area, which nine possible implications of the research can address.